Influence of Longan Wood Biochar on the Growth of Pure White Hokkaido Sweet Corn and Siamese Ruby Queen Corn - Lucha, Kitti; Mahasorasak, Phattharakorn; Ariyadet, Chalinda; Sutigoolabud, Pathipan; Sangchyoswat, Chanchai; Susawaengsup, Chanthana; Aroonsrimorakot, Syam (Interdisciplinary Research Review, 2023)
Background: Sweet corn is a cash crop that can be grown all year round, which is considered as one of the causes of soil fertility degradation. Biochar is a highly porous material, able to absorb water and nutrients well. It has the potential to be used as an ingredient in soil improvement. The objective of this study was to investigate the effect of Longan wood biochar on the growth of Hokkaido Pure White Sweet Corn and Queen Ruby Siam. Method: A completely randomized design was conducted by dividing into experimental kits according to the strain of sweet corn. Each strain has a ratio of Longan wood biochar mixed in 0% (control), 5% and 10% of planting material. Result: The results showed that the ratio of longan wood biochar was 10% of planting material which had higher stem, higher reproductive growth and found to have significant differences statistically. Conclusion: Studies revealed that using biochar as an ingredient in planting material can help increase the growth and yield of Hokkaido Pure White Sweet Corn and the Siamese Ruby Queen, as well as reduce agricultural waste.